2017
DOI: 10.1002/term.2449
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun silk fibroin‐based neural scaffold for bridging a long sciatic nerve gap in dogs

Abstract: Silk fibroin (SF)-derived silkworms represent a type of highly biocompatible biomaterial for tissue engineering. We have previously investigated biocompatibility of SF with neural cells isolated from the central nervous system or peripheral nerve system in vitro, and also developed a SF-based nerve graft conduit or tissue-engineered nerve grafts by introducing bone marrow mesenchymal stem cells, as support cells, into SF-based scaffold and evaluated the outcomes of peripheral nerve repair in a rat model. As an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…In the last decades, much effort has been made to construct NGCs with autograft‐like structures using advanced material design and fabrication techniques. Tissue engineering‐based strategies including the use of various biomaterials, specific growth factors, modified cells as well as physical stimuli have been extensively researched to construct diverse NGCs, from simple hollow tubes to complex conduits that incorporated with contact guidance cues . Several NGCs based on collagen (COL) (NeuraGen), polyglycolic acid (Neurotube), and polylactide‐ε‐caprolactone (Neurolac) have achieved US Food and Drug Administration approval for widespread production .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, much effort has been made to construct NGCs with autograft‐like structures using advanced material design and fabrication techniques. Tissue engineering‐based strategies including the use of various biomaterials, specific growth factors, modified cells as well as physical stimuli have been extensively researched to construct diverse NGCs, from simple hollow tubes to complex conduits that incorporated with contact guidance cues . Several NGCs based on collagen (COL) (NeuraGen), polyglycolic acid (Neurotube), and polylactide‐ε‐caprolactone (Neurolac) have achieved US Food and Drug Administration approval for widespread production .…”
Section: Introductionmentioning
confidence: 99%
“…Conducive to cell respiration and gas penetration [26] Cross-linked porosity Can meet the need of cutting [27,28] Mechanical strength Similar to human skin tissue [40] 2 Journal of Nanomaterials epithelial regeneration of tissue [48]. Therefore, CS-based nanocomposites are widely used in wound healing, tissue engineering, and drug delivery [49].…”
Section: Ideal Characteristic Advantage Referencesmentioning
confidence: 99%
“…At the same time, synthetic polymers also have the shortcoming of lacking cell binding sites. Natural materials such as gelatin [36], collagen [37], cellulose [38], chitosan [39], silk fibroin [40], mainly from plants, and animals have excellent biocompatibility, and there are biological sites on the surface that can be specifically recognized by cell integrins which can promote cell adhesion migration and proliferation and accelerate tissue regeneration and reconstruction [41]. Biological dressings not only have better water permeability and air permeability but also can resist the invasion of bacteria and prevent infection.…”
Section: Introductionmentioning
confidence: 99%
“…Benfenati et al demonstrated that SF preserved neuronal physiology of the dorsal root ganglion, which in turn promoted peripheral nerve regeneration. Xue et al designed a SF‐based neural scaffold containing silk fibers to bridge a 30 mm‐long sciatic nerve gap in dogs, and the experimental group achieved satisfactory regenerative outcomes that were close to those obtained by bridged using autologous nerve grafts at 12 months of surgery. We blended SF with poly (l‐lactide‐co‐ɛ‐caprolactone) [P(LLA‐CL)] and fabricated a SF/P(LLA‐CL) nerve conduit to construct the segmental nerve in rats.…”
Section: Introductionmentioning
confidence: 97%
“…Silk fibroin (SF) is a promising natural biopolymer in the biomedical field with remarkable biocompatibility, biodegradability, and mechanical flexibility . SF‐based nerve conduits have been widely used to repair peripheral nerve defects and produced encouraging results both in vitro and in vivo . Benfenati et al demonstrated that SF preserved neuronal physiology of the dorsal root ganglion, which in turn promoted peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%